Characteristics of Sago in the Maluku Islands (Taxonomy, Morphology, Species, and Productivity) - Riry, Roberth Berthy (JENDELA PENGETAHUAN, 2022)
Sago is a very potential plant in the Maluku Islands, is a natural wealth that is bestowed by God for some Maluku people and has played an essential role for the community since ancient times, both as a staple and additional food as well as its function as a building material and its role in environmental sustainability, especially water management control. The area of sago land in the Maluku Islands is currently 58,185 ha; it is likely to be even broader if a detailed inventory process is carried out. With this area, the potential for sago starch in Maluku reaches 465,180 tons/year, and only 46,000 tons/year has been utilized, or about 10%, which means that 90% of sago starch is lost in the forest yearly. On the other hand, public attention to sago is decreasing or even disappearing, especially in urban communities. Urban communities generally eat less "papeda" and "sago plates." An introduction to several aspects of sago, especially the taxonomic, morphological, species, and productivity aspects of sago in the Maluku Islands to the younger generation. It is hoped that the younger generation will realize sago's many benefits and uses, thus trying to get to know the sago plant more profoundly and being determined to develop it into a leading commodity in Maluku.